EFFECTS OF PROTEIN SUPPLEMENTATION ON CARDIORESPIRATORY, METABOLIC, IMMUNOLOGICAL, RENAL VARIABLES AND BODY COMPOSITION IN THE ELDERLY (CIPEEX, 2023)
The aging process is associated with impairments in strength, lean mass (LM), cardiovascular health(CH), and cardiorespiratory health (CRH), due to metabolic, hemodynamic, and body compositionchanges in the elderly. The implications of these changes within the aging process can have their effectsmitigated through nutritional intervention. To test this hypothesis, a randomized clinical trial wasdetermined to be conducted at the Evangelical University of Goiás (UniEVANGÉLICA), where elderlyvolunteers (60 to 85 years old) will be randomized (n = 40/group) into groups (1) Control (no proteinsupplementation), group (2) Supplementation (only protein supplementation). The supplementationprotocol will be carried out for 3 months, and the evaluations will take place before the start of theprotocol and after 3 months. Numerous cardiovascular, pulmonary, immunological, renal, muscular, andhematological parameters will be evaluated. The analyses will be expressed as mean and standarddeviation. A significance level of p≤0.05 will be adopted for comparisons made in the paired T-test andfor multiparametric analyses. It is expected that the effects of the protein supplementation protocol willsignificantly improve the parameters described above, bringing positive results for the elderly volunteersin the study.
Keywords: Elderly; protein supplementation; metabolism; hemodynamic processes